Parameters affecting outcome of paediatric cardiomyopathies in the intensive care unit: experience of an Egyptian tertiary centre over 7 years. Issue 1 (1st January 2020) - Sobeih, Alaa A.; El-Saiedi, Sonia A.; Abdel Khalek, Noha S.; Attia, Shereen A.; Hanna, Baher M.
ABSTRACT: Introduction : Paediatric cardiomyopathies are rare but serious and often life-threatening conditions. In the absence of cardiac transplant and ventricular assist device as treatment options in our region, it is very important to identify patients at higher risk. The aim of this study was to determine the outcome of patients diagnosed with cardiomyopathies and their prognostic indicators. Patients and methods : This study included 92 cases representing all patients diagnosed with cardiomyopathy who were admitted into the pediatric cardiac intensive care unit during the period from January 2012 to September 2018. The patients were classified into two groups according to the outcome: the first group comprised 69 patients who survived, and the second group comprised 23 patients who died. All medical records were reviewed, and data were recorded and analysed. Results : Patients with cardiomyopathies represented 8.6% (92/1071) of all patients with cardiac diseases who were admitted in the study period and in the target age group (0.5–12 years). Dilated cardiomyopathy (DCM) was the most frequent type of cardiomyopathy among the admitted patients (80 patients), while 6 patients were diagnosed with hypertrophic cardiomyopathy (HCM), 4 were diagnosed with restrictive cardiomyopathy (RCM), and only 2 were diagnosed with mixed DCM-RCM. Seventy patients required inotropic support (76.1%). Assisted mechanical ventilation was used on 15 patients (16.3%). Twenty-three patients (25.0%) died during the 7-year study period. Conclusions Conclusions The occurrence of hypotension, abnormally high liver enzymes, the need for mechanical ventilation and the need for multiple inotropic drugs were found to be statistically significant predictors of mortality, while age, sex, fractional shortening, ejection fraction, presence of mitral regurgitation, mural thrombus, electrolyte disturbance and arrhythmias did not predict or affect patients' outcomes.